Older adults' perspectives of smart home technology: Are we developing the technology that older people want?. Issue 147 (March 2021) - Ghorayeb, Abir; Comber, Rob; Gooberman-Hill, Rachael
Highlights: The study explored older people's views and expectations of smart home technology. The article presents a comparison between six participants recruited from the community and seven who had experience of living with smart home technology for eight to twelve months. Participants have different understandings of smart home technologies. Among participants who had already tried the smart home monitoring technology, acceptance increased over time and with use. They expressed fewer concerns than non smart homes participants regarding privacy, trust, usability, and more concerns about utility. The article suggests some insights to assist with improving the technology adoption and ageing in place. Abstract: New technology and smart homes have the potential to improve quality of life, safety, and care for older people. However, we do not yet know how older people's perceptions of these technologies may vary, in particular how views based on experience of actual use may differ from those related to anticipated use. We also do not know how older people living independently might view technology that may be of future rather than current value to them. This paper explores older people's views of smart home monitoring technology and compares these between people with direct experience and those without. Four focus groups were conducted with six older people recruited from the community with no smart home experience and seven drawn from a large-scale Interdisciplinary Research Collaboration that is developing a sensor platform for health and lifestyle at home. For the seven participants, the sensor platform was installed and operated in their homes for eight to twelve months before the current study. The study found that participants in each group had some similar and some different understandings of smart home technologies. Among participants who had already tried the smart home monitoring technology, acceptance increased over time and with use. They expressed fewer concerns than non smart homes participants regarding privacy, trust, usability, and more concerns about utility. Non smart home participants focused on the extent to which this technology might increase household's vulnerability and they considered the technology somewhat intrusive and noticeable. It appeared that the more positive views of participants who had direct experience of smart homes related to the degree of trust between them and the researchers who installed and maintained the smart home system. Both groups of participants shared views about the technical feasibility, affordability, impact on relationships, and about the engagement and competencies of those who would view the monitoring data. They suggested that the technology would be more acceptable if it was possible to customize functionality and features. These findings have implications for development of smart home technologies so that they are appropriate and acceptable to older people who are living independently.